DESIGNING A SERVICE AND INFORMATION SYSTEM FOR BRIDAL MAKE-UP ARTISTS (MUA) BASED ON ANDROID - Wijaya, Satria Aji; Deviyana, Riska; Briliant, Muhamad; Lestari, Kanti; Sari, Dwi Puspita (Universitas Islam Negeri Raden Intan Lampung, 2022)
Make-up service ordering services still use sms and telephone as a medium of communication between customers and professional make-up artists (MUA). An MUA used to offer or promote his services through Facebook, Instagram and so on. The use of these media is still ineffective. Less information is obtained so that the customer difficult to get services that suit their tastes or needs and are difficult to adjust to MUA. The purpose of Make-up for changing fashionable face which is judged to be less than perfect and for embellishing fashionable face especially for women to present at event or events such as weddings. The research method in this research is qualitative research where strategic is used is design and creation. This study used data collection methods and interviews, observations and literature studies. The design method used is the waterfall and the testing techniques used are Black Box and White-Box. From this research become a result the design of the make-up service centre application displays a list of MUA profiles on the MUA Makhsun Photography Gisting make-up service, the prices offered and customers can check the availability of make-up made based on android that can be accessed using a smartphone, The design this application wised giving information about Make-up service centre and also make it easier to find and order make-up services according to the needs of customers or users.